2006
DOI: 10.3354/dao073023
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of marine viral haemorrhagic septicaemia virus isolated from the Flemish Cap by nucleotide sequence analysis and restriction fragment length polymorphism patterns

Abstract: A total of 14 viral haemorrhagic septicaemia virus (VHSV) isolates obtained from Greenland halibut Reinhardtius hippoglossoides caught at the Flemish Cap, a fishing ground in the North Atlantic Ocean near Newfoundland, were characterised using restriction fragment length polymorphism (RFLP) and nucleotide sequence analysis. RFLP analysis was performed on a 1259 bp fragment of the glycoprotein (G) gene, and a 305 nucleotide region within the nucleoprotein (N) gene was used for sequence analysis. Representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…Upon infection of the host, the 6 genes are transcribed progressively from the 3' to 5' end of the template viral RNA, and in decreasing molar frequencies (Kurath & Leong 1985). Therefore, due to the initial position of the N-gene in the VHSV genome, N transcripts are the most abundant during viral infection and therefore have been the target of several molecular assays used to detect VHSV (López-Vázquez et al 2006, Matejusova et al 2008, Cutrín et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Upon infection of the host, the 6 genes are transcribed progressively from the 3' to 5' end of the template viral RNA, and in decreasing molar frequencies (Kurath & Leong 1985). Therefore, due to the initial position of the N-gene in the VHSV genome, N transcripts are the most abundant during viral infection and therefore have been the target of several molecular assays used to detect VHSV (López-Vázquez et al 2006, Matejusova et al 2008, Cutrín et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The third VHS virus genotype (III) represents isolates from marine fish species in Kattegat, Skagerrak and the North Sea [8] and a member of this genotype was in the autumn of 2007 associated with about 10% mortality in a rainbow trout farm in western Norway [9,10]. VHS virus genotype III has been found in eel ( Anguilla anguilla ), cod ( Gadus morhua ), herring ( Clupea harengus ), sprat ( Sprattus sprattus ), haddock ( Melanogrammus aeglefinus ), Norway pout ( Trisopterus esmarkii ), poor cod ( Trisopterus minutus ), blue whiting ( Micromesistius poutassou ), withing ( Merlangius merlangus ), turbot ( Scophthalmus maximus ), greenland halibut ( Reinhardtius hippoglossoides ) and lesser argentine ( Argentina sphyraena ) [cf [3,5,8,11]]. The outbreak of VHS in Norway is the first time an isolate belonging to genotype III is found in rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…For Atlantic salmon, this finding was perhaps not surprising since, in Europe, the detection of VHSV in this species is very rare, including only a single isolation of virus in Spain (Jimenez de la Fuente et al 1988), which was further characterized by Lopez-Vazquez et al (2006b). In addition, results of experimental infection trials using bath immersion showed that all types of VHSV are non-or lowly pathogenic to Atlantic salmon (Skall et al 2005).…”
Section: Discussionmentioning
confidence: 97%